PERAYAAN MAULID DICIKOANG:SELAYANG PANDANG TAREKAT DI MAKASSAR - Supratman, Supratman; masdiana, masdiana (Universitas Hasanuddin, 2014)
Sayyid Jalaluddin al-Aidid was the 27th generation descendant of the Prophet, from Iraq, whom'Sayyid Community' attributed to him in Cikoang. The teachings of Sayyid Jalaluddin Al-Aidid are a heavily mystical dimension that is